Implementation of Metapolije as a mapping tool for marketing distribution data - Purbaningtyas, Rani; Oktavian, Siska Aprilia; Albaab, Mochammad Rifki Ulil; Hartanto, Sugeng (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
Information regarding marketing distribution data plays a crucial role for business actors in formulating their future business strategies. Marketing distribution data enables companies to perform market segmentation more accurately. By understanding the characteristics and preferences of consumers in each segment, companies can tailor their products and marketing messages to meet specific consumer needs. MetaPolije serves as an alternative solution for mapping marketing distribution data. MetaPolije is a web-based platform designed to facilitate user access. It was developed using the Scrum software development method, which consists of four main phases: planning, sprint, sprint review, and sprint retrospective. MetaPolije provides information about the profiles of objects in a given area, along with comprehensive demographic data for that area. The data visualization displays maps down to the sub-district level, which is customized according to partner requests. Similarly, the various categories of objects shown can be adjusted based on user partner requirements. The demographic data displayed comes from the Sidoarjo Regency Statistics Agency (BPS). Therefore, whenever the Sidoarjo Regency BPS releases the latest population data, the MetaPolije platform updated also. The information presented on the MetaPolije platform can be utilized by policymakers to better understand consumers and for crafting marketing strategies that are more suitable and relevant based on existing data. By utilizing MetaPolije, businesspeople gained better data visualization regarding the types of businesses currently present in a particular area. With the support of available demographic data, it can assist in making subsequent decisions related to appropriate business development policies moving forward.